2011
DOI: 10.1007/s00426-011-0397-5
|View full text |Cite
|
Sign up to set email alerts
|

Gaze behaviour during space perception and spatial decision making

Abstract: A series of four experiments investigating gaze behavior and decision making in the context of wayfinding is reported. Participants were presented with screen-shots of choice points taken in large virtual environments. Each screen-shot depicted alternative path options. In Experiment 1, participants had to decide between them in order to find an object hidden in the environment. In Experiment 2, participants were first informed about which path option to take as if following a guided route. Subsequently they w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 52 publications
(64 reference statements)
5
84
0
1
Order By: Relevance
“…Regarding the former, there is a growing body of cartographic research reported in the psychology literature on spatial concepts (e.g. Liben & Downs, 1993;Wiener, Hölscher, Büchner, & Konieczny, 2012) and spatial abilities (e.g. Hegarty, Montello, Richardson, Ishikawa, & Lovelace, 2006;Miyake, Friedman, Rettinger, Shah, & Hegarty, 2001).…”
Section: Psychologymentioning
confidence: 99%
“…Regarding the former, there is a growing body of cartographic research reported in the psychology literature on spatial concepts (e.g. Liben & Downs, 1993;Wiener, Hölscher, Büchner, & Konieczny, 2012) and spatial abilities (e.g. Hegarty, Montello, Richardson, Ishikawa, & Lovelace, 2006;Miyake, Friedman, Rettinger, Shah, & Hegarty, 2001).…”
Section: Psychologymentioning
confidence: 99%
“…It was shown in consumer and cognitive science research that a person's gaze can be highly predictive of future actions in selection tasks. Various researchers found that if people are asked to make a decision between a number of options, there is a significant gaze bias towards the chosen option for a short time period before the decision is announced [3,17,25,26]. It is also known that the gaze direction leads the walking direction by a few seconds [6] and the same holds true for driving [8,12].…”
Section: Related Workmentioning
confidence: 99%
“…There is ample evidence that the processing of spatial information such as landmarks is dependent on and affected by gaze behavior (e.g., Wiener, De Condappa, & Hölscher, 2011;Wiener, Hölscher, Büchner, & Konieczny, 2012).…”
Section: Introductionmentioning
confidence: 99%